Shortest Path Navigation Optimization using Algorithm A* in GPS-Based Augmented Reality Visualization - Aswandi, Nopan; Hendrik, Billy; Arlis, Syafri (Universitas Putra Indonesia YPTK Padang, 2025)
The development of digital technology in the Society 5.0 era encourages the integration of technology-based solutions in various fields, including higher education. Ibnu Sina University faces challenges in providing informative and accurate access to campus navigation, especially for new students and visitors. The lack of a directional system and the absence of a digital map of the campus cause difficulties in finding service locations such as the rectorate, academic room, or finance department. Conventional technologies such as Google Maps have not been able to provide specific navigation in the campus environment due to the limitations of internal building mapping. This research aims to develop a campus navigation system based on Augmented Reality (AR) and Global Positioning System (GPS) that is optimized with the A* (A-Star) algorithm for the determination of the shortest path. AR technology is used to display visual directions in real-time in a real environment through a smartphone camera. GPS plays a role in determining the user's position, while the A* algorithm calculates the shortest route based on the structure of the campus location graph using a heuristic approach. The development method used is the Multimedia Development Life Cycle (MDLC) which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. Data collection was carried out through direct observation, interviews with the campus, and recording 14 coordinate points of campus service locations using Google Earth. The system is built using the Unity platform with support from the AR Foundation and ARLocation, as well as the A* implementation in route search. The results of this research are able to provide a more efficient, accurate, and interactive campus navigation solution. This system not only supports the convenience of users in finding a location, but also becomes an innovation in the development of campus services based on digital technology.